Strategi Coping Terhadap Stress Kerja Pada Perawat di Rumah Sakit: Literatur Review - Rina Hardiyanti; Iman Permana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: Increased work stress on nurses is caused by the high demands of work and must be maximal in serving patients at the hospital. Nurses are required to have a way of completing and adjusting conditions to the problem which is usually referred to as coping, so that they can carry out their professional work professionally. Objective: To find out the coping strategies used by nurses in dealing with work stress in the hospital environment. Method: This literature review uses database the Ebsco, Google Scholar, DOAJ, and Pubmed. At the beginning of the search with keywords: